2016
DOI: 10.1080/15299732.2016.1225626
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical experience, diagnosis, and theoretical orientation in the treatment of posttraumatic and dissociative disorders: A vignette and survey investigation

Abstract: Controversy exists regarding the merits of exposure-based treatments for posttraumatic stress disorder (PTSD) versus a phased approach when prominent dissociative symptoms are present. The first aim of this study was to examine the degree to which diagnosing dissociation in two traumatized patients' vignettes influenced clinicians' preference for phase-oriented treatment and whether clinicians' treatment experience contributed to their treatment preference. The second aim was to assess the extent to which part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Seventy percent of adults with a confirmed DD diagnosis believed they had been sometimes or frequently misdiagnosed, 35% had sought treatment from six or more clinicians prior to diagnosis, and 83% reported clinicians had skeptical or antagonistic attitudes about dissociation (Leonard et al, 2005). Dorahy et al (2017) reported similar findings. They presented a vignette that included all diagnostic criteria for dissociative identity disorder (DID), except dissociative identities, to mental health professionals; only 60% of clinicians diagnosed a DD.…”
Section: Underdiagnosis Of Dissociationmentioning
confidence: 98%
“…Seventy percent of adults with a confirmed DD diagnosis believed they had been sometimes or frequently misdiagnosed, 35% had sought treatment from six or more clinicians prior to diagnosis, and 83% reported clinicians had skeptical or antagonistic attitudes about dissociation (Leonard et al, 2005). Dorahy et al (2017) reported similar findings. They presented a vignette that included all diagnostic criteria for dissociative identity disorder (DID), except dissociative identities, to mental health professionals; only 60% of clinicians diagnosed a DD.…”
Section: Underdiagnosis Of Dissociationmentioning
confidence: 98%
“…At least 12 studies have found that clients with a history of trauma wish therapists would directly inquire about their traumatic experiences and recommend that staff receive training to improve their ability to compassionately ask about it (see Trevillion et al, 2014 for a review). However, a lack of trauma training among mental health professionals—including not learning how to assess for a history of trauma using clinical interviews or psychological tests—has been documented (e.g., Brand, Schielke, Brams, & DiComo, 2017; Brand, Webermann, & Frankel, 2016; Dorahy et al, 2017; Xiao, Gavrilidis, Lee, & Kulkarni, 2016). This lack of trauma training is problematic, as there is a possibility that failing to recognize trauma-related symptoms or failing to adequately focus on the impact of trauma in session could result in misdirected or harmful treatment (Dorahy et al, 2017).…”
Section: Lack Of Trauma Training Among Professionalsmentioning
confidence: 99%
“…The lack of training is exacerbated by information about trauma and dissociation in undergraduate and graduate textbooks that is often inadequate, inaccurate, sensationalized, or fails to present a balanced review of research (Brand, Kumar, & McEwen, 2019 ; Reinders & Veltman, 2020 ; Wilgus, Packer, Lile-King, Miller-Perrin, & Brand, 2016 ). Even seasoned clinicians may believe they understand and know how to identify the impacts of trauma, including dissociation, yet many clinicians cannot accurately diagnose DDs when presented with vignettes that describe cases with clear dissociative symptoms (Dorahy et al, 2016 ). Indeed, clinicians may feel quite confident they are correctly diagnosing a traumatized individual, when in fact, they are incorrect (Perniciaro, 2015 ).…”
Section: Introductionmentioning
confidence: 99%